Students' Numeracy Literacy Skills In Mathematics Learning In Elementary School As A Foundation For The Future - Linda Kurnia Aprilliani; Dina Pratiwi Dwi Santi (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
Numeracy is a critical skill as a provision and foundation for students for the future. Numerical literacy skills will help students deal with life problems when they shop or examine the information, ideas, and problems they face more deeply, so they can draw conclusions and solve problems appropriately. This research aims to analyze numeracy skills in mathematics learning in elementary school. This research uses a descriptive qualitative method. The data collection technique in this study used a 3-item description test, The indicators of numeracy skills include: 1) Using various kinds of numbers and symbols related to basic mathematics to solve problems in various contexts of daily life; 2) Using mathematical reasoning in problem-solving and communicating; 3) Selecting and applying appropriate and simple problem-solving strategies, and presenting situations. Data was also gathered through interviews with fifth-grade homeroom teachers. The research subjects were 18 fifth-grade students of SDN Kesenden. Data analysis techniques in the form of an average percentage of each indicator of numeracy skills obtained were 50% for the first, 52% for the second, and 52% for the third. Based on the results of the average data analysis on each indicator, the numeracy skills of fifth-grade students of SDN Kesenden obtained a result of 51%, which means that the numeracy skills of students are at the medium category level.